Features of the physique in young martial arts athletes - Bovykin, S. S.; Godina, E. Z.; Khomyakova, I. A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the features of the physique of young martial arts athletes aged 9-13 years.